Reduction of vibrations of pedestrian bridges using Tuned Mass Dampers (TMD) - FIEBIG, Wiesław (Archives of Acoustics, 2010)
The reduction of structural vibrations on the example of two pedestrian bridges (in Poznań and Wrocław) with using of tuned mass dampers (TMD) has been presented in the paper. The results of theoretical and experimental studies of pedestrian bridge vibrations has been described and discussed. Basing on the results of calculations and measurements, tuned mass dampers (TMD) has been designed and mounted in the structure of the bridges. The measurements after the assembly of TMD show a high efficiency of vibration damping.